The impact of behavioral symptoms of burnout on work engagement of older employees: The case of Slovenian companies - Maja Rožman; Sonja Treven; Marijan Cingula (Naše gospodarstvo / Our Economy, 2018)
The main objective of the paper is to determine the impact of behavioral symptoms of burnout of older employees on their work engagement in large- and mediumsized companies in Slovenia. The research is based on the implementation of a factor analysis by which we wanted to reduce the large number of variables into a smaller number of factors. With those factors, we performed a simple linear regression. Based on the results, we confirmed the hypothesis that behavioral symptoms of burnout of older employees have a statistically significant negative impact on their work engagement. Well-being of employees of varying ages in the workplace is key for long-term effectiveness of companies. From this point of view, companies should apply appropriate measures to reduce burnout as well as to contribute to employees' well-being and better workplace performance, which is reflected in work engagement of employees.
Keywords: J24; I19; C38; 330; burnout; behavioral symptoms of burnout; older employees; work engagement